RURAL REVITALIZATION THROUGH TIBETAN TRADITIONAL SPORTS HERITAGE - Wei , Zhang (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
The intangible cultural heritage, deeply rooted in history and tradition, holds a significant place within the rich tapestry of Chinese culture. In the wake of the 18th National Congress of the Communist Party of China, there has been a growing recognition of the contemporary relevance and value of China’s enduring cultural heritage. This cultural legacy serves as a powerful source of inspiration and guidance as China embarks on a new era of building a modern socialist nation and pursuing the Chinese Dream. The preservation and promotion of China’s fine traditional culture have taken on renewed importance, not only as a means of cultivating cultural confidence but also as a vehicle for enhancing China’s global cultural presence. As the nation strives to achieve its second centennial goal, the role of fine traditional culture in fostering unity, identity, and progress cannot be overstated. This article explores the enduring significance of China’s intangible cultural heritage in the context of contemporary socio-political and cultural developments. It delves into the ways in which this heritage serves as a source of cultural pride, national identity, and global engagement, contributing to the broader goal of fully realizing a modern socialist China